Hyperbaric treatment of platelets extends in vitro storage to 14 days. Issue 9 (2nd August 2022) - Kelly, Kathleen; Sen, Sharon; Ilyin, Ilya; Dumont, Larry J.
Abstract: Background: Platelets for transfusion have a storage time of 5–7 days at 22°C–24°C, which results in a strain on the supply chain and supply shortages. We describe a novel method to extend platelet storage using xenon (Xe) gas under high pressure and refrigeration. Study Design and Methods: Apheresis platelets (APU) prepared in 65% platelet additive solution (PAS) were stored under standard conditions (SC) at 20°C–24°C to Day 5. Paired APUs were prepared with Xe and stored to Day 14 at 2°C–6°C under hyperbaric conditions (XHC). A standard panel of in vitro assays was conducted. Results: XHC platelets were viable out to Day 14. The average pH of Day 14 platelets was 6.58, and 86% maintained some degree of swirl compared with 7.02 and 100% swirl for Day 5 SC platelets. The rate of glycolysis was reduced under XHC storage with less glucose consumption and lactate generation. Activation levels for Day 14 platelets, while increased, did not prevent response to agonists in vitro, including epinephrine + Adenosine 5‐Diphosphate (EPI/ADP) and thrombin receptor‐activating peptide (TRAP) aggregation. Thromboelastogram (TEG) assessment showed 80% or greater conservation of platelet function for Day 14 xenon stored platelets compared with Day 5 SC platelets. Discussion: Platelet storage with the Xe/hyperbaric/cold method is a feasible candidate for extension of storage to 14 days based on in vitro characteristics. In vivo recovery and survival studies are indicated. The capability to extend platelet storage to 14 days would make large strides toward resolving issues of platelet outdating for prophylactic use.